(untitled) (Prilozi za orijentalnu filologiju, 2017)
Vakufnamas (Endowment Charters) are the first class sources for studying the history of cities during the Ottoman period. They contain a whole range of important data on the urban development of cities, construction of different buildings, religious, educational and humanitarian facilities, as well as the population structure, development of different trades, etc. The original Vakufnama of Hadži İsmail, son of Husein Halifa from Sarajevo (second decade of the month of Rejeb, 1050 (1640)), that is published here for the first time is kept at the Gazi-Husrev-bey’s Library, in the register of endowment charters, nr. 60, page 319. It is written in Turkish, quite readable, but contains a considerable number of mistakes. At the beginning, this Vakufnama contains the verification of its transcript done by contemporary Sarajevo kadi, Muhammed, son of Abdurahman. The introductory part (exposition) contains the reflections of the founder on earthly life and its evanescence, streaked by the quotes from Koran and hadises. It is followed by disposition (main part) which explains what is being endowed and under what conditions. By this document, the founder Hadži İsmail, son of Husein Halifa, inhabitant od Jahja-pasha’s mahala in Sarajevo, endowed ali his money for the funeral costs, studying of the Holly Koran, and for the reparation of the fountain and road in Pazarić. Final part of Vakufnama contains the verification by kadi, that proves the validity of the endowment, and names of the witnesses, who can prove the regularity of the document.